Ecological and biological characteristics of Betula pendula in the conditions of urban environment - PetrushkevуchY. M.; KorshуkovI. I. (Regulatory Mechanisms in Biosystems, 2020)
This study focused on the influence of polluted environment on various indicators of Betula pendula Roth and their applicability to the bioindication of the condition of urban environments in one of the largest industrial cities of Ukraine in the steppe zone, namely Kryvyi Rih. Our investigations have been carried out for three years (2016–2018) in eight B. pendula plantations exposed to different levels of aerotechnogenic loading: to a low pollution level – in Kryvyi Rih Botanical Garden of the National Academy of Sciences of Ukraine (control), Poliana Kazok Square and Heroiv ATO Park, to an average pollution level – along three highways with heavy traffic and those exposed to a high pollution level – near the enterprises of Private JSC ‘Northern Iron Ore Dressing Works’(Northern GZK) and Public JSC ‘ArcelorMittal Kryvyi Rih’. Morphometric, anatomical and statistical methods were used to identify the most sensitive indicators of the impact of air pollutants. As a result of this research, changes associated with greater level of technogenic pollution were revealed in the morphological and anatomical parameters of the leaf blade, namely: reduction in the length of the petiole to 14.3%, in the length of the leaf blade to 8.4% and its width to 12.8%; a decrease in length, width and area of the stomata up to 29.4%, 25.9%, 48.1%, respectively; an increase in thickness of the leaf blade to 23.0% and its tissues, as well as the stomata density per 1 mm2 of the leaf to 47.3%. We also registered a decrease in the length of male catkins to 7.4% and an increase in their width to 13.7% associated with greater environmental pollution. The maximum and minimum values of the indicators were recorded near the mining and processing works and close to metallurgical plants. In addition, in order to determine the most sensitive indicators of B. pendula response to urban pollution, we carried out a comparative analysis of all the studied parameters and those, the results of which were published earlier. As a result of this analysis, these indicators were ranked according to the level of differences in relation to the control values in decreasing order: differences in 1.5 and more times in comparison with the control – seed germination, curved leaf apex, fluctuating asymmetry, crown volume, pollen viability, the amount of abnormal pollen, vital state of trees, seed quality, crown area; 25–50% differences from control – stomata area, thickness of the lower epidermis, stomata density on leaf blade, seed productivity, pollen fertility, width of fruit (female) catkins, number of scales in fruit (female) catkins, thickness of palisade parenchyma, tree height, stomata length, pollen tube length, trunk diameter at the height of 1.3 m, thickness of the upper epidermis, stomata width; a 10–24% change in indicators – leaf thickness, length of fruit (female) catkin petiole, weight of 1000 seeds, leaf petiole length, male catkin width, leaf blade width, fruit (female) catkin length; the differences from control are less than 10% – the thickness of the spongy parenchyma, the polar axis of pollen, the leaf length, the equatorial diameter of pollen, the length of male catkins and the purity of the seeds.